2004
DOI: 10.1007/s00167-004-0537-1
|View full text |Cite
|
Sign up to set email alerts
|

Report of experience in 190 patients with the use of closed suction drainage in arthroscopic knee procedures

Abstract: The goal of this study is to report our experience with the use of suction drainage for various arthroscopic knee procedures. One hundred and ninety patients who underwent arthroscopic knee procedures participated in the study, and were divided into two groups (Group 1: Suction drainage, Group 2: No suction drainage). For every patient, the following parameters were recorded: age, gender, operative time, tourniquet or pump use, the amount of fluid collected in the hemovac drain, presence of meniscal tear, type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 15 publications
1
11
0
Order By: Relevance
“…Our rate is similar to those reported for other cartilage repair techniques such as microfracture and ACI, which show effusions from 5% to 31% [12,28]. Tatari et al found drilling of the osteochondral surface led to higher amounts of fluid and bleeding owing to the penetration of the subchondral bone in comparison to nondrilling [35]. They recommended suction drainage to prevent subsequent effusions in these arthroscopic procedures [35].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Our rate is similar to those reported for other cartilage repair techniques such as microfracture and ACI, which show effusions from 5% to 31% [12,28]. Tatari et al found drilling of the osteochondral surface led to higher amounts of fluid and bleeding owing to the penetration of the subchondral bone in comparison to nondrilling [35]. They recommended suction drainage to prevent subsequent effusions in these arthroscopic procedures [35].…”
Section: Discussionsupporting
confidence: 85%
“…Tatari et al found drilling of the osteochondral surface led to higher amounts of fluid and bleeding owing to the penetration of the subchondral bone in comparison to nondrilling [35]. They recommended suction drainage to prevent subsequent effusions in these arthroscopic procedures [35]. All of our patients had improvement at [31].…”
Section: Discussionmentioning
confidence: 65%
“…Tatari [15] in his study of 57 patients who underwent partial meniscectomy, found that none of them presented significant effusion at 4, 7 nor 15 days after the procedure. Concordantly, our group found similar results with 92% of patients not presenting significant effusion at 7 days post intervention.…”
Section: Discussionmentioning
confidence: 98%
“…[19] Contrarily, Tatari proposed that although use of drains can improve the vision, they are unnecessary for partial meniscectomy, cartilage repair, or limited synovial plica excision operations. [20] In addition, drains cannot keep the pressure stable in the knee joint. [21] Suspensory irrigation cannot provide clear vision, because the drainage may be blocked by the subcutaneous tissue and joint capsule under the lateral edge of the incision.…”
Section: Discussionmentioning
confidence: 99%